1988
DOI: 10.1210/endo-123-5-2201
|View full text |Cite
|
Sign up to set email alerts
|

Release of Growth Hormone Binding Protein from IM-9 Lymphocytes by Endopeptidase is Dependent on Sulfydryl Group Inactivation*

Abstract: The hydrophilic GH-binding protein of serum is a derivative of the GH receptor. Little is known how this GH binding protein is released from the receptor which is firmly anchored in the plasma membrane. The IM-9 lymphocytes provide a useful laboratory model for studying this process because they are richly endowed with GH receptors and, under special conditions, are able to shed these receptors during incubation. Incubation of IM-9 cells for 90 min at 30 C did not result in the appearance of significant [125I]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(57 citation statements)
references
References 17 publications
3
54
0
Order By: Relevance
“…3B), supporting the suggestion that the inhibition of PMA-induced GHBP shedding by these inhibitors may be a direct result of inhibition of proteolytic cleavage of GHR at the cell surface. Cell-permeable sulfhydryl-reactive alkylating reagents, such as iodoacetamide or NEM, were previously shown to promote proteolytic cleavage of GHBP (Trivedi & Daughaday 1988, Massa et al 1993, Amit et al 1994, Harrison et al 1995, Bick et al 1996, Alele et al 1998. Thus, it was important to test whether BB-3103 and Ro31-9790 could also inhibit NEM-induced GHBP shedding from the CHO/hGHR cell line, since another metalloprotease inhibitor, IC3, was shown to inhibit GHBP shedding from IM-9 cells (Alele et al 1998).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3B), supporting the suggestion that the inhibition of PMA-induced GHBP shedding by these inhibitors may be a direct result of inhibition of proteolytic cleavage of GHR at the cell surface. Cell-permeable sulfhydryl-reactive alkylating reagents, such as iodoacetamide or NEM, were previously shown to promote proteolytic cleavage of GHBP (Trivedi & Daughaday 1988, Massa et al 1993, Amit et al 1994, Harrison et al 1995, Bick et al 1996, Alele et al 1998. Thus, it was important to test whether BB-3103 and Ro31-9790 could also inhibit NEM-induced GHBP shedding from the CHO/hGHR cell line, since another metalloprotease inhibitor, IC3, was shown to inhibit GHBP shedding from IM-9 cells (Alele et al 1998).…”
Section: Resultsmentioning
confidence: 99%
“…We and others have demonstrated that sulfhydryl-reactive agents markedly induced GHBP release from IM-9 human lymphocytes (Trivedi & Daughaday 1988, Massa et al 1993, Alele et al 1998, Hep G2 human hepatoma cells (Amit et al 1994, Harrison et al 1995 and Chinese hamster ovary (CHO) cells transfected with rabbit or human GHR (hGHR) (Bick et al 1996, Amit et al 1999. We then suggested that the increased release of GHBP might be a consequence of alkylation of one or more free sulfhydryl group(s) on an endopeptidase that apparently becomes activated to induce GHBP shedding (Amit et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mouse, GHR and GHBP mRNA with alternative 5 -UTRs are differentially expressed in mouse liver and placenta (Southard et al 1995). In humans and rabbits, the circulating GHBP probably arises from the proteolytic cleavage of the membrane receptors (Leung et al 1987, Trivedi & Daughaday 1988, Sotiropoulos et al 1993, Bingham et al 1994. In the chicken, it appears that the serum GHBP is produced from proteolytic cleavage of the membrane receptors rather than from alternative splicing of the cGHR gene (Cogburn et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Based on a study with the IM9 lymphoma cell line, which exhibits somatogenic receptors for GH, it was postulated that the extracellular domain of the GH-receptor is shed from the cell by a limited proteolytic cleavage [7]. On the other hand, separate mRNAs were ascribed for GH-BP and the GH-receptor in the mouse [8] and rat [5], probably generated by alternative splicing of DNA.…”
mentioning
confidence: 99%